Future Studies: Dimensions and Components in the Educational System of a University of Medical Sciences - Monireh Parvaneh; Kiomars Niaz Azari; Taraneh Enayati (Kerman University of Medical Sciences, 2021)
Background: One way to make change in the field of education is through future studies. Considering the role of future studies in building a better future for the country's medical education and health system, the establishment of the required bases in medical education is necessary.Objectives: The present study aimed to investigate the dimensions and components of future studies in the educational system of a university of medical sciences.Methods: In this grounded-theory study, the statistical population included expert and knowledgeable faculty members with an experience of delivering services as directors, principals, and deputies of the faculties of Babol University of Medical Sciences, Mazandaran, Iran. In-depth and exploratory individual interviews were held through a questionnaire containing six standard items within October and December 2018.The interview process was completed based on the data saturation law, and the required conclusion was drawn with 10 samples.Results: A questionnaire with 50 components in three main dimensions, including infrastructure (25 components), management and faculty members (9 components), and outputs (16 components), was designed. Moreover, the validity and reliability of the questionnaire were confirmed.Conclusion: It is time to build necessary capacities for future studies in the universities of medical sciences and provide the possibility for extensive participation and support of researchers and faculty members in future studies programs in the field of medical education and health research in Iran. The dimensions and components obtained from this study can be helpful in this regard.